A new genus and a new species of Ectrichodiinae from French Guiana and an updated key to the genera of the New World (Hemiptera, Reduviidae) - Hélcio R. Gil-Santana; Jader Oliveira; Jean-Michel Bérenger (ZooKeys, 2020)
Amazopothea guilberti gen. nov. et sp. nov. belonging to the subfamily Ectrichodiinae is described based on male and female specimens from French Guiana. An updated key to the New World genera of Ectrichodiinae is provided.